ANALISIS UJI KUAT SINYAL TERHADAP JARAK JANGKAU MAKSIMAL SISTEM PENERIMAAN SINYAL INTERNET BERBASIS EDIMAX HP-5101ACK - ., Defti Widya Amalia (Faculty of Engineering, Universitas Tanjungpura, 2018)
The development of telecommunication technology is currently improving. Almost each person has telecommunication device; it is seen in the increasing of cellular phone uses as the communication media in society. In a cellular communication system, electromagnetic wave will propagate and connect one device to another. The reflections of some objects from mobile station movement causes the signal strength received from mobile station varied and the path loss may occur in signal receiving. Path loss is the propagated path loss (rugi-rugi lintasan propagasi) from the electromagnetic wave that spreads through the space marked by the power level differences received by MS from EIRP emitted by BTS. The reflection happened when the propagating electronic wave hit or struck an object with bigger dimension compared to the electromagnetic wavelength. The reflection happened because of the soil surface, buildings, and walls. This research was conducted in three different BTS locations, each BTS has 3 measuring location points, makes total 9 measuring points in this research. This research consists of path loss calculation using Hatta propagation model, Okumura-Hatta, Cost-231 and Walfisch-Ikegami. For Hatta model, the smallest path loss finding was located in Alex Griya complex which was 0.9 dB, for Okumura-Hatta the smallest path loss finding was in Wijayasari alley, for Cost-231 model was in Pemda II alley which was 2.51 dB and for Walfisch-Ikegami was in Merdeka Timur Street with path loss value 0.05 dB. The more far the sender’s distance with the receiver, the bigger obstacle chance in data sending, therefore it can be concluded the more far the distance, the bigger path loss found. This research also designed programs to count the path loss using Graphical User Interface (GUI) matrix laboratory. Key words: Path Loss, Propagation Model, Hatta Propagation, Okumura-Hatta, Cost-231, Walfisch-Ikegami